Teacher self-efficacy and self-reported cognitive activation and classroom management: A multilevel perspective on the role of school characteristics. (December 2021) - Holzberger, Doris; Prestele, Elisabeth
Abstract: In the present study, we consider teachers' self-efficacy as indicator for teacher motivation on the teacher level and at the school-level. We examine the interplay of teachers' individual self-efficacy (subscales classroom management and instruction) with school-level efficacy and more-external school characteristics (collaboration, instructional leadership, and participation) when predicting teachers' self-reported cognitive activation and classroom management. Austrian TALIS 2018 data from 4255 teachers at 246 schools were analyzed. Multilevel analyses revealed relationships between teachers' self-efficacy and self-reported cognitive activation and classroom management both, at the teacher and school levels. For self-reported cognitive activation, no significant context effect or cross-level interaction was found. Classroom management differed depending on whether a teacher was situated in a low- or a high-efficacy school (context effect). Also, teacher collaboration moderated the association of teachers' self-efficacy and their self-reported classroom management (cross-level interaction). The findings indicate the importance of addressing the school context when investigating teacher self-efficacy. Highlights: Schools with high school-level efficacy demonstrate higher instructional quality. Cognitive activation independent of school characteristics. Teachers in high-efficacy schools report higher classroom management (context effect). (Non-systematic) cross-level interactions with regard to self-reported classroom management.